Social and communication skills in English through virtual or simulated environment - Wan Fara Adlina Wan Mansor, 1963-; Universiti Teknologi Malaysia. Fakulti Pengurusan dan Pembangunan Sumber Manusia (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references